Distribution of extended-spectrum β-lactam, quinolone and carbapenem resistance genes, and genetic diversity among uropathogenic Escherichia coli isolates in Tehran, Iran. (September 2018) - Shahbazi, Shahla; Asadi Karam, Mohammad Reza; Habibi, Mehri; Talebi, Atefeh; Bouzari, Saeid
Highlights: High antimicrobial resistance in uropathogenic Escherichia coli (UPEC), especially multidrug resistance. Majority of UPEC harboured extended-spectrum β-lactamase (ESBL) genes, especially bla TEM and bla CTX-M . All of the UPEC isolates were negative for carbapenemases by the modified Hodge test and PCR. Some associations between virulence factors and antimicrobial resistance. There was great clonal diversity among the UPEC isolates by PFGE. Abstract: Objectives: Antimicrobial resistance among uropathogenic Escherichia coli (UPEC) is increasing. The aim of this study was to evaluate antimicrobial resistance in UPEC isolates and its correlation with virulence factors. Methods: A total of 120 E. coli isolates were collected from patients with urinary tract infection in Tehran, Iran. Biofilm formation and antimicrobial susceptibility were determined by phenotypic tests. The combination disk diffusion test and modified Hodge test (MHT) were performed for phenotypic detection of extended-spectrum β-lactamases (ESBLs) and carbapenemases, respectively. PCR was used for the detection of virulence genes, ESBL-encoding genes, and quinolone ( qnr) and carbapenem resistance genes. Pulsed-field gel electrophoresis (PFGE) was performed to explore the genetic relatedness among isolates. Results: Most isolates exhibited biofilm formation, and different frequencies of virulence genes were observed. There was a high rate of resistance, especially multidrug resistance, to most of the antimicrobial agents tested. Phenotypically, 67.5% of the isolates produced an ESBL and were resistant to different antimicrobial classes. In total, 83.3% of the isolates harboured ESBL genes, especially bla TEM and bla CTX-M, and 32.5% were positive for the quinolone resistance genes qnrS and qnrB . All isolates were negative for carbapenemases by the MHT and PCR. These results indicate the association between the presence of various virulence genes and antimicrobial susceptibility. PFGE analysis showed that there was great clonal diversity among the selected isolates, with 17 isolates divided into five clusters. Conclusions: These results indicate that the high antimicrobial resistance among UPEC isolates is alarming and requires urgent attention.